Fecal Microbiota Transplant From Highly Feed Efficient Donors Affects Cecal Physiology and Microbiota in Low- and High-Feed Efficient Chickens - Metzler-Zebeli, Barbara U.; Siegerstetter, Sina-Catherine; Magowan, Elizabeth; Lawlor, Peadar G.; O′Connell, Niamh E.; Zebeli, Qendrim (Frontiers in Microbiology, 2019)
Fecal microbiota transplants (FMT) may be used to improve chicken’s feed efficiency (FE) via modulation of the intestinal microbiota and microbe-host signaling. This study investigated the effect of the administration of FMT from highly feed efficient donors early in life on the jejunal and cecal microbiota, visceral organ size, intestinal morphology, permeability, and expression of genes for nutrient transporters, barrier function and innate immune response in chickens of diverging residual feed intake (RFI; a metric for FE). Chicks (n = 110) were inoculated with the FMT or control transplant (CT) on 1, 6 and 9 days posthatch (dph), from which 56 chickens were selected on 30 dph as the extremes in RFI, resulting in 15 low and 13 high RFI chickens receiving the FMT and 14 low and 14 high RFI chickens receiving the CT. RFI rank and FMT only caused tendencies for alterations in the jejunal microbiota and only one unclassified Lachnospiraceae genus in cecal digesta was indicative of high RFI. By contrast, the FMT caused clear differences in the short-chain fatty acid (SCFA) profile in the crop and cecal microbiota composition compared to the CT, which indicated alterations in amylolytic, pullulanolytic and hemicellulolytic bacteria such as Lactobacillus, Dorea and Ruminococcus. Moreover, the FMT caused alterations in intestinal development as indicated by the longer duodenum and shallower crypts in the ceca. From the observed RFI-associated variation, energy-saving mechanisms and moderation of the mucosal immune response were indicated by higher jejunal permeability, shorter villi in the ileum, and enhanced cecal expression of the anti-inflammatory cytokine IL10 in low RFI chickens. Relationships obtained from supervised multigroup data integration support that certain bacteria, including Ruminococcocaceae-, Lactobacillus- and unclassified Clostridiales-phylotypes, and SCFA in jejunal and cecal digesta modulated expression levels of cytokines, tight-junction protein OCLN and nutrient transporters for glucose and SCFA uptake. In conclusion, results suggest that the intestine only played a moderate role for the RFI-associated variation of the present low and high RFI phenotypes, whereas modulating the early microbial colonization resulted in long-lasting changes in bacterial taxonomic and metabolite composition as well as in host intestinal development.